Lymphocyte and NK Cell Counts Can Predict Sepsis-Associated Delirium in Elderly Patients - Li, Dongkai; Zhang, Jiahui; Bai, Guangxu; Chen, Jianwei; Cheng, Wei; Cui, Na (Frontiers in Aging Neuroscience, 2021)
Background: Sepsis-associated delirium (SAD) is prevalent in elderly patients and is recognized as brain dysfunction associated with an increased inflammatory response in the central nervous system during sepsis. Neuroinflammation was demonstrated to be part of its mechanism and we aimed to validate the role of immunity imbalance in a combined retrospective and prospective cohort study. Methods: We performed a retrospective study analysing the association between SAD and lymphocyte counts in the peripheral blood, alongside a prospective trial evaluating the quantitative changes in lymphocyte subsets and their predictive value for early diagnosis of SAD. Results: In the retrospective study, among 1,010 enrolled adult patients (age ≥65 years), 297 patients were diagnosed with delirium during intensive care unit (ICU) stay and lymphocyte counts at ICU admission in the SAD group were significantly higher than in non-delirious counterparts (1.09±0.32 vs. 0.82±0.24, respectively, p=0.001). In the prospective study, lymphocyte counts (0.83 (0.56, 1.15) vs. 0.72 (0.40, 1.06)×109/L, p=0.020) and NK cell counts (96 [68, 118] vs. 56 [26, 92] cells/μl, p=0.024) were significantly higher in the SAD group. The area under the curve value of natural killer (NK) cell count was 0.895 (95% confidence interval [CI]: 0.857, 0.933) and of lymphocyte count was 0.728 (95% CI: 0.662, 0.795). A NK cell count cut-off value of 87 cells/ml in septic patients at ICU admission was predictive of delirium with a sensitivity of 80.2% and specificity of 80.8%. Conclusions: We found that lymphocyte and NK cell counts were significantly higher in senior patients with SAD and that NK cell count may be valuable for prediction of SAD within elderly patient cohorts.